Determination of Tripamide in human urine by high-performance liquid chromatography and high-performance liquid chromatography/electrospray ionization tandem mass spectrometry - Kim, Y; Hwang, J; Kim, M; Lee, W (JOHN WILEY & SONS LTD, 2003)
Tripamide is a drug widely used in clinical practice for the treatment of hypertension and edema. This work evaluated a screening method for Tripamide and its urinary metabolites in human urine, using high-performance liquid chromatography diode-array detection (HPLC/DAD). Identification of these metabolites was investigated by high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (HPLC/ESI-MS/MS) after dosing with 15 mg Tripamide. Acid hydrolysis showed that Tripamide is conjugated in the body. Two suspected metabolites were detected by HPLC/DAD. HPLC/ESI-MS/MS analysis suggested that these metabolites were probably hydroxylated together with loss of the -NH2 group and dehydrogenation. These results will be useful in confirmation methods for Tripamide in doping control. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: PLASMA; METABOLITES; FUROSEMIDE